Competências e habilidades requeridas na formação do cirurgião-dentista: percepção de professores e alunos - Silva, Cristiane Pereira Cabral da (2010)
When discussing the aspects that involve the health sector, training of human resources has been a subject of great interest. In this context, dealing specifically Dentistry, debate the role of courses in the training in oral health and its integration into the labor market. We conducted a descriptive exploratory case study, of qualitative and quantitative approach, aiming to meet, discuss and evaluate the process of implementing national curriculum guidelines at the UFSM dental clinic. We used a questionnaire with 30 closed questions, based on the competencies and skills required for the training of professional oral health. We performed a focus group technique too. Participated in the research scholars and teachers of the 9th and 10th periods. The data were analyzed descriptively. For the focus group we used the content analysis. The results suggested that the students feel better prepared than teachers consider them, both in technical skills and skills with specificity in public health. In relation to individual skills and competencies, both students and teachers stand out as the best preparation that deals with the fulfillment of basic investigations and operative procedures, and poor preparation in planning and administration of health community services. The preparation of the UFSM Dentistry student may be compromised as the egress profile of the dentist, with generalist, humanist, critical and reflective and work on all levels of health care, as advocated in the National Curriculum Guide.